2021
DOI: 10.1590/1980-265x-tce-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Interfere in the Quality of Life Related to the Health of Women in the Postpartum Period in Northeastern Brazil

Abstract: Objective to analyze the sociodemographic, obstetric, type of delivery and professional factors that provided care that can influence the quality of life related to women's health in the immediate puerperium period. Method cross-sectional, correlational study conducted in a reference maternity hospital, with 272 women in the immediate puerperium period hospitalized in the rooming-in accommodation. A sociodemographic, clinical and obstetric questionnaire and the Short Form Health Survey-36 scale were used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
7
Order By: Relevance
“…This finding is similar to Ali's study, which revealed that unwanted and unplanned pregnancies can reduce women's quality of life [ 49 ]. A study conducted in Northeastern Brazil reported similar findings, which reveals that non-acceptance of pregnancy, was associated with lower health-related QoL scores [ 31 ]. Similarly, the finding is consistent with Woolhouse's research, which found that women who planned their pregnancy had higher health-related QOL scores among postpartum women [ 47 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This finding is similar to Ali's study, which revealed that unwanted and unplanned pregnancies can reduce women's quality of life [ 49 ]. A study conducted in Northeastern Brazil reported similar findings, which reveals that non-acceptance of pregnancy, was associated with lower health-related QoL scores [ 31 ]. Similarly, the finding is consistent with Woolhouse's research, which found that women who planned their pregnancy had higher health-related QOL scores among postpartum women [ 47 ].…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, many women are typically unaware of the long-term mental and physical health problems that can occur as a consequence of pregnancy, childbirth, and puerperium; as a result, they are unprepared when such problems arise, and their QoL (quality of life) will be harmed for an extended period of time [ 29 ]. The majority studies on postpartum health QoL have been conducted in developed countries [ 13 , 30 , 31 ], with few in developing countries [ 32 ], and there are no adequate studies that examined postpartum health-related QoL among Ethiopian women, with the exception of one study conducted in Arba-Minch, Ethiopia [ 33 ], which is limited on physical and mental health problems. As a result, this study provides a good picture of the factors influencing maternal health QoL and attempted to investigate the influencing factors for maternal health-related QoL through postpartum women in Jimma Town, including physical, psychological, and social problems.…”
Section: Introductionmentioning
confidence: 99%
“…Todavia, a mulher deve ser apta de ressignificar sua função no processo parturitivo, concedendo que ela estabeleça sobre a forma de parto pautado em informações e evidências científicas, sendo relevante, nesta fase, o envolvimento do enfermeiro no cuidado ao ciclo gravídico-puerperal, pois este profissional tem habilidades estratégicas no processo educativo, somado a isso, a humanização satisfatória a mulher (RIBEIRO et al, 2021).…”
Section: Resultsunclassified
“…In the same context, another study with 150 of Egyptian women (75 with natural childbirth and 75 with caesarean section) women also revealed the same results, supporting the current one and estimated better QOL among women with a natural childbirth as compared to women with cesarean section 27 . Another research with 272 women in the initial postpartum period in the state of Piauí, northeastern Brazil, evaluated the QOL of women in the postpartum period and the professional that provided the care showed that the average of mental health of women after normal delivery performed by nurses was higher when compared with the normal delivery performed by doctors (75,86), with statistical significant (p=0,005) 28 .…”
Section: /12mentioning
confidence: 99%